Evaluation of a steroid delivery system to mitigate the severity of proliferative vitreoretinopathy in a minipig model - Wong, Chee Wai; Cheung, Ning; Howden, James S.; Busoy, Joanna Marie Fianza; Sim, Shaun; Lim, Joshua; Ho, Candice; Veluchamy, Amutha Barathi; Storm, Gert; Wong, Tina T. (Frontiers in Ophthalmology, 2023)
To investigate the efficacy of liposomal prednisolone phosphate to mitigate the severity of proliferative vitreoretinopathy (PVR) in a minipig model of PVR.Eighteen eyes of 9 minipigs underwent PVR induction surgically. Eyes were randomized equally into 3 groups: Intravitreal injection of liposomal prednisolone phosphate (LPP), triamcinolone acetonide (TA), and controls. PVR severity was graded on fundoscopic examination using a modified version of the Silicon Study Classification System. Severe PVR was defined as grade 2-5 on this classification, and the proportion of eyes with retinal detachment from severe PVR, defined as retinal re-detachment i.e. PVR grade 2-5 was compared between treatment and control groups.On day 28, 5 eyes (83.3%) in the control group were observed to have severe PVR. Within the LPP group, 1 (16.7%) eye developed retinal detachment due to severe PVR. Grade 0 PVR was observed in 4 (66.7%) eyes, grade 1 in 1 (16.7%) eye and grade 5 in 1 (16.7%) eye. Within the TA group, grade 0 PVR was observed in 4 eyes (66.7%), grade 1 in 2 eyes (16.6%) and grade 5 in 1(16.7%) eye. The difference in proportion of eyes with severe PVR was significantly lower in the LPP group compared to controls at day 28 (16.7% vs 83.3%, p=0.02). There was no significant difference in the rate of severe PVR or median PVR grade between the liposomal prednisolone phosphate and triamcinolone acetonide groups.Liposomal prednisolone phosphate reduces severity of PVR in a minipig model of PVR. Deleted: ¶ Deleted: Eighteen eyes of 9 Gottingen minipigs were used for this 129 study. Age range was 1 year ± 3months and weight range was 15-130 25kg… 131